Meeting report of the sixth annual tri-service microbiome consortium symposium - Ida G. Pantoja-Feliciano De Goodfellow; Richard Agans; Robyn Barbato; Sophie Colston; Michael S. Goodson; Rasha Hammamieh; Kristy Hentchel; Robert Jones; J. Philip Karl; Robert Kokoska; Dagmar H. Leary; Camilla Mauzy; et al. (Environmental Microbiome, 2023)
Abstract The Tri-Service Microbiome Consortium (TSMC) was founded to enhance collaboration, coordination, and communication of microbiome research among DoD organizations and to facilitate resource, material and information sharing amongst consortium members, which includes collaborators in academia and industry. The 6th Annual TSMC Symposium was a hybrid meeting held in Fairlee, Vermont on 27–28 September 2022 with presentations and discussions centered on microbiome-related topics within seven broad thematic areas: (1) Human Microbiomes: Stress Response; (2) Microbiome Analysis & Surveillance; (3) Human Microbiomes Enablers & Engineering; (4) Human Microbiomes: Countermeasures; (5) Human Microbiomes Discovery - Earth & Space; (6) Environmental Micro & Myco-biome; and (7) Environmental Microbiome Analysis & Engineering. Collectively, the symposium provided an update on the scope of current DoD microbiome research efforts, highlighted innovative research being done in academia and industry that can be leveraged by the DoD, and fostered collaborative opportunities. This report summarizes the activities and outcomes from the 6th annual TSMC symposium.